The Students’ Attitude and Learning Experience toward Flipped Classroom Implementation During COVID-19 Outbreak: A Survey Study - Betaubun, Marta (FKIP Universitas Lampung, 2021)
The Students’ Attitude and Learning Experience toward Flipped Classroom Implementation in ESP Class during COVID-19 Outbreak: A Survey Study. Objective: This study was to determine student attitudes and learning experiences related to the application of Flipped Classroom (FC) in English for Specific Purposes (ESP) classes during the COVID-19 pandemic. Method: A quantitative approach is used in this study by taking respondents from four classes of students in the engineering faculty at a university in Papua. Respondents of this study amounted to 200 who fill online questionnaire. The responses obtained were then analyzed using SPSS 23. Findings: Based on data analysis, students had a neutral attitude and have a reasonably good level of learning experience towards the application of FC. Conclusion: Application of FC strategies has benefits to be applied, especially in learning during the pandemic COVID-19.Keywords: flipped classroom, student attitudes, learning experiences, digital learning, COVID-19. DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202105